Ambient and indoor air pollution exposure and adverse birth outcomes in Adama, Ethiopia. (June 2022) - Flanagan, Erin; Oudin, Anna; Walles, John; Abera, Asmamaw; Mattisson, Kristoffer; Isaxon, Christina; Malmqvist, Ebba
Graphical abstract: Highlights: Associations of ambient NOX/2, cooking fuel and fetal/neonatal death were explored. Overall, results were statistically insignificant and inconclusive. A tendency towards an association for ambient NOX/2 and fetal death was suggested. No associations were found for cooking fuel type and either adverse birth outcome. Abstract: Air pollution poses a threat to human health, with pregnant women and their developing fetuses being particularly vulnerable. A high dual burden of ambient and indoor air pollution exposure has been identified in Ethiopia, but studies investigating their effects on adverse birth outcomes are currently lacking. This study explores the association between ambient air pollution (NOX and NO2 ) and indoor air pollution (cooking fuel type) and fetal and neonatal death in Adama, Ethiopia. A prospective cohort of mothers and their babies was used, into which pregnant women were recruited at their first antenatal visit (n = 2085) from November 2015 to February 2018. Previously developed land-use regression models were utilized to assess ambient concentrations of NOX and NO2 at the residential address, whereas data on cooking fuel type was derived from questionnaires. Birth outcome data was obtained from self-reported questionnaire responses during the participant's postnatal visit or by phone if an in-person meeting was not possible. Binary logistic regression was employed to assess associations within the final study population (n = 1616) using both univariate and multivariate models; the latter of which adjusted for age, education, parity, and HIV status. Odds ratios (OR) and their corresponding 95% confidence intervals (CI) were reported. Within the cohort, 69 instances of fetal death (n = 16 miscarriages; n = 53 stillbirths) and 16 cases of neonatal death were identified. The findings suggest a tendency towards an association between ambient NOX and NO2 exposure during pregnancy and an increased risk of fetal death overall as well as stillbirth, specifically. However, statistical significance was not observed. Results for indoor air pollution and neonatal death were inconclusive. As limited evidence on the effects of exposure to ambient air pollution on adverse birth outcomes exists in Sub-Saharan Africa and Ethiopia, additional studies with larger study populations should be conducted.